Subject and Time: Jean Luc Marion’s alteration of Kantian Subjectivity - Alvis, Jason; Novoa Rojas, Francisco (Resonancias. Revista de Filosofía, 2023)
This text examines Jean-Luc Marion’s alteration of Kantian subjectivity. Marion challenges the notion of a stable and autonomous subject, arguing that the subject must be in constant relation with the excessive and the other. He rejects the Cartesian ego cogito and seeks a reconception of being in relation to the other and the transcendent. Marion emphasizes the importance of love as the center of subjectivity and suggests that the subject’s primary concern is not self-subsistence but love and being loved. The text explores the implications of this perspective in relation to temporality and phenomenological manifestation. Marion proposes a reconfiguration of the subject that is revealed in the relation with the excessive and the co-constitution with the other.